Periodontal disease and obesity in an Indian population - Giri, DK; Kundapur, PP; Bhat, GS; Bhat, KM; Guddattu, V (Nepal Journal of Medical Sciences, 2013)
Background: Associations between obesity and several chronic inflammatory diseases are emerging. Research from some parts of the world has also indicated that a relationship between periodontal disease and obesity is possible. The aim of the present study was to determine the association of obesity with periodontal disease in a semi urban Indian population. Methods: Body Mass Index (BMI) was determined for 323 patients visiting the department of Periodontics. Other demographic variables such as age, gender, stress, educational background and smoking were also considered. Clinical examination of the periodontal health was assessed using the Plaque index (PI), the Gingival index (GI) and the Community Periodontal Index (CPI). Results: No association was obtained between BMI and periodontitis. Other demographic variables were also not significantly related. Lower gingival index scores, were significantly associated with better periodontal health. Conclusion: Good oral hygiene and normal body weight can reduce the overall inflammatory burden, thereby reducing the risk for development of periodontal disease. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 144-148 DOI: http://dx.doi.org/10.3126/njms.v2i2.8965